Potencialidades e desafios para o aproveitamento de agregado siderúrgico de escória de aciaria em países em desenvolvimento: uma revisão sistematizada da literatura - Abreu, Leonardo Dias de (2023)
As a result of the growing worldwide demand for natural aggregate in the civil construction sector, there is a search for replacement of recycled aggregates originated by the steel slag production in public infrastructure works. However, legal, environmental, economic, monitoring and control barriers have been reported as hindering the use of this waste, leaving its destination for industrial landfills in developing countries. Thus, to shed light on the main difficulties reported in the literature, a systematic bibliographic and document review was carried out, delimited in the period 2019 to 2022, using the Smart Bibliometrics tool. Among the main barriers, the lack of public policies or transparency and instability of those that exist, unavailability of data on industrial waste management, lack of specific environmental guidelines for the reuse and recycling of these wastes, challenging economic conditions, aging infrastructure and structures stand out, decision support tools unavailable to support and guide management decisions. From this, was represented through a cause-and-effect diagram, the interrelations between the elements identified in the literature and the use of steel slag. The results, based on this research, demonstrated that the political and normative elements were those that presented the highest frequency in citations regarding the promotion of the steel slag use, with a significant presence verified in 58% of the articles, followed by the elements economic (24%), operational elements (13%) and finally physical elements (5%). Political and normative elements, specifically in terms of obligation, are preferred and generally have greater relevance in relation to the others, being the ones that have most influenced greater use, in addition to presenting a series of potentially positive aspects for the use of alternative aggregates.